Novel TTN Mutation Causing Severe Congenital Myopathy and Uncertain Association with Infantile Hydrocephalus - Palanikumar Balasundaram; Indirapriya Darshini Avulakunta; Leslie Delfiner; Paul Levy; Katie R. Forman (Case Reports in Genetics)
Arthrogryposis multiplex congenita (AMC) is characterized by nonprogressive symmetric contractures of multiple joints with normal intellect and normal systemic examination. AMC is often due to fetal akinesia, which has neurologic, muscular, and connective tissue etiologies. We present a case of AMC due to a variant in the titin (TTN) gene in a term neonate. The infant is homozygous for this variant, c.38442dup, which is predicted to result in a truncated protein (p.Pro12815Thr fs∗37, NM_001267550.2). A literature search (PubMed) failed to find reports of this TTN variant. The variant was classified as pathogenic and submitted to ClinVar. Titin is the body’s largest protein, expressed in skeletal and cardiac muscles and encoded by the TTN gene. Due to its large size (364 exons), the TTN gene has been difficult to sequence; the number of variants in the TTN gene and the spectrum of titinopathies are probably underestimated.